Credibility of a salesperson in retailing: judgments on the basis of their demographic parameters - S. Urbonavicius; V. Dikcius; J. Reardon (Marketing i Menedžment Innovacij, 2016)
The aim of the article. The study aims to add the scientific and managerial knowledge about the fit between buyer and salesperson, by analyzing judgments of buyers about salespeople, based just on visual information. The results of the analysis. Buyers evaluate credibility of salespeople based on a relatively large number of their characteristics, forming factors of salesperson credibility. The result of this evaluation predetermines whether an advice of this person is to be considered, and, subsequently, whether the purchase will be made. The decision whether to ask for an assistance of a salesperson is often made spontaneously, based just on a visual presence of a salesperson. The stereotyping of visual impressions can be limited to the age and genders of a salesperson, and out of these characteristics potential buyers derive believes about personal and professional characteristics of a salesperson, and develop overall judgments regarding the trustfulness of the recommendations. In the study, three research questions have been analyzed: RQ1: How evaluations of salesperson credibility differ, depending on his/her age and gender?; RQ2: What dimensions of salesperson credibility have influenced higher or lower judgments about the overall credibility of salespeople who have different demographic characteristics?; RQ3: How evaluations of credibility of salespeople, who differ in age and gender, vary depending on the age and gender of buyers? Respondents have been shown four pre-tested pictures of salespeople, who differ among themselves in terms of their age and gender. The age categories matched to those of the respondents; two salespeople (male and female) represented younger adults, two others – elder adults. The research instrument measured eight dimensions of salesperson credibility: Attractiveness, Experience, Dynamism, Comprehensiveness, Objectiveness, Sincerity, Expertise, and Accommodation on a seven point Likert scale. RQ1. Repeated measures ANOVA with a Greenhouse-Geisser correction determined that perception of credibility was different. Post hoc tests using the Bonferroni correction revealed that the younger male salesperson was evaluated better than other salespeople. RQ2. Repeated measures ANOVA with a Greenhouse-Geisser correction used to find differences of characteristics among the four salespeople. Surprisingly, the younger male has been perceived as the best expert among the four; post hoc tests using the Bonferroni correction showed his evaluation being significantly higher than of the others. The younger male together with the elder female were superior on evaluation of the experience and sincerity; the evaluation of younger male salesperson has been evaluated the best on the dimension of dynamism. RQ3. Analysis performed with factorial ANOVA for each type (age/gender combination) of a salesperson. Elder female salesperson. The difference was found on Gender, Age and Age*Gender interaction. Female respondents evaluated this salesperson as more credible than male; younger respondents were more positive than elder respondents. The interaction showed that 38-57 male respondents evaluated credibility of this salesperson less positively, than all others. Younger female salesperson. Statistically significant difference occurred as the effect of Age and Age*Gender interaction. The elder group of respondents evaluated this salesperson as more credible than younger respondents. Male respondents evaluated credibility lower than female respondents. Younger male salesperson. The statistical difference was found for the main effect of the Age and Age*Gender interaction. The elder respondents evaluated this salesperson as more credible than younger ones. Interaction analysis disclosed that younger male respondents were skeptical about credibility of this salesperson than females. Elder male salesperson. The difference has occurred just for the main effect of the Age; we only observed that the elder respondents (38-57) evaluated this salesperson as more credible than the younger respondents. Conclusions and directions of further researches. The study helped researching the dyadic fit between buyers and salespeople, based on their age and gender, in regard of evaluation of salesperson credibility. Some findings go into the contradiction with the knowledge about the buyer-seller similarity, and even with the similarity-attraction paradigm.